Thyroid status in patients with early stages of cancer of various localization - V. A. Bandovkina; E. M. Frantsiyants; A. M. Salatova; M. A. Еngibaryan; V. L. Volkova; N. D. Cheryarina (Исследования и практика в медицине, 2024)
Purpose of the study. To determine the thyroid status of primary cancer patients in the early stages of uterine body cancer, kidney cancer, breast cancer, skin melanoma and lung cancer without a history of endocrine pathology.Patients and methods. The content levels of thyroid-stimulating hormone (TSH), thyroid hormones (THs) T4 and T3 of total and free forms were determined in the blood serum by RIA method in 132 patients with breast cancer, uterine body cancer, lung cancer, kidney cancer and skin melanoma (average age 55 years). The comparison group consisted of practically healthy donors.Results. Only in skin melanoma, serum TSH levels were reduced by 1.5 times (p < 0.05). The T4 content was reduced by 1.4–1.7 times (p < 0.05) in uterine body cancer and kidney cancer, increased in lung cancer patients and 16 % of breast cancer patients by 1.4–1.7 times though (p < 0.05). A 1.3–1.5‑fold low (p < 0.05) T3 level was found in breast cancer, kidney cancer, and skin melanoma, while an 1.6‑fold increase (p < 0.05) was found in uterine body cancer. The revealed changes in THs by the type of clinical hyperthyroidism are an increase of 1.8 times (p < 0.05) FT3 on the background of low TSH in the blood in patients with skin melanoma, and by the type of hyperthyroxinemia in patients with lung cancer and breast cancer, consisting in increased concentrations of T4 and FT3, and with free and total T3 levels in patients uterine body cancer, as well as FT4, without changes in TSH in the blood serum of patients, may be associated with the features of malignant pathology, since it is known that THs are proliferation stimulants and can build up in tumors.Conclusion. The development of a malignant tumor even in the early stages of the disease is perceived by the body as a threat for homeostasis and the response to the occurrence of neoplasm is the reaction of the hypothalamicpituitary-thyroid regulatory axis. As an outcome, patients develop euthyroid disorder syndrome.